Sexuality, body image and relationships following burns: Analysis of BSHS-B outcome measures - Connell, Kylie; Phillips, M.; Coates, Rosemary; Doherty-Poirier, Maryanne; Wood, F. (Pergamon, 2014)
BackgroundThe Burns Specific Health Scale – Brief (BSHS-B) was analyzed to investigate the longitudinal impact of burns on sexuality and body image. Four sub-domains of the BSHS-B domains were of particular interest: sexuality, body image, affect and relationships, and as such were investigated for correlation between all of the sub-scales of the BSHS-B.MethodsA total of 1846 observations from 865 Western Australian burn patient BSHS-B questionnaires were analyzed. Descriptive statistical methods included dichotomous and ordinal scale variables and medians, as well at the range for continuous variables. Inferential statistical methods used longitudinal linear mixed-effects models and random effects models with the BSHS-B total and its sub-scales as dependent variables.ResultsThe four BSHS-B domains of interest all showed no significant change over time, indicating that the psychological and psychosocial impact of burns does not significantly improve for burn survivors, regardless of good physical and functional recovery.ConclusionsBurn survivors experience sexuality, body image and relationship changes following a burn, which may affect their quality of life (QoL) over time. Rehabilitation services need to be aware of these issues and create rehabilitation programs that specifically and meaningfully address these issues for burn survivors.